Application of a staging model in patients with obsessive–compulsive disorder: cross-sectional and follow-up results. (30th April 2022) - Benatti, Beatrice; Lucca, Giulia; Zanello, Riccardo; Fesce, Fabio; Priori, Alberto; Poloni, Nicola; Callegari, Camilla; Fontenelle, Leonardo F.; Dell'Osso, Bernardo
Abstract: Introduction: Obsessive-compulsive disorder (OCD) is a prevalent and disabling condition with frequent chronic course. Staging models applied to psychiatric disorders seek to define their extent of progression at a particular time-point and differentiate early, milder clinical phenomena from those characterizing illness progression and chronicity. In OCD patients, a staging model has been recently proposed but not tested yet. This was the aim of the present study. Methods: From an overall sample of 198 OCD patients, recruited across two psychiatric clinics in Northern Italy, 70 patients on stable treatment completed a follow-up assessment ranging from 12 to 24 months. At follow-up initiation, patients had been divided into four staging groups, according to the model proposed by Fontenelle and Yucel. At the end of the follow-up, patients were subdivided into three groups (no stage change, improved stage, or worsened stage) compared with statistical analyses. Results: At the end of the follow-up, 67.1% patients showed no stage changes, 24.3% a stage improvement, and 8.6% a stage progression. Worsened patients showed higher rates of comorbid disorders and higher rates of unfavorable employment characteristics compared to the other subgroups ( P < .05). Patients with worsened stage showed higher prevalence of somatic obsessions ( P < .05), while patients with improved stage showed higher rates of magical thinking and violence/harm obsessions compared to other groups ( P < .05). Discussion: The present results provide epidemiologic and clinical correlates of the first application of a staging model in a sample of OCD patients, encouraging further studies to assess the utility of this approach in the field.